Analytics of ESPCam on Arduino-Based Automatic Clothesline Protectors - Agung Kridoyono; Aris Sudaryanto; Dimas Sasongko; Akhmad Dicky Harianto (Jurnal Informatika Polinema, 2022)
The ability to recognize weather conditions, such as rain or heat, is a main feature of the automatic clothesline. In previous research we developed an automatic clothesline that can recognize weather conditions using rain sensors and LDR with a success rate of 80% (Dicky et al. 2022). To be more convincing, in this research we added ESPCam to be able to see clothes and the weather visually, so that users can ascertain the weather conditions. This research focuses on implement ESPCam to the automatic clothesline system and testing its reliability. With ESPCam, users can view streaming, store visual image data, and turn on or off the flash LED. System testing is done by sending a command to turn on streaming on the system, followed by a command to turn on or turn off the flash LED. Based on the test data, the success rate of ESPCam used in the system reached 96.665%.